MODIS NDVI trends and fractional land cover change for improved assessments of vegetation degradation in Burkina Faso, West Africa. (June 2018) - Zoungrana, Benewinde J-B.; Conrad, Christopher; Thiel, Michael; Amekudzi, Leonard K.; Da, Evariste Dapola
Abstract: Reduction of natural vegetation cover in the savannah of West Africa constitutes a pressing environmental concern that may lead to soil degradation. With the aim to assess the degradation of natural vegetation in the savannah of Burkina Faso, this study combined NDVI trends and fractional Land Use/Cover Change (LULCC). Fractional LULCC maps, derived from the aggregation of a 30 m Landsat LULCC map (1999–2011) to 250 m resolution of MODIS, were used to assess natural vegetation conversions in the small-scale spatial patterns of savannah landscapes. Mann-Kendall's monotonic trend test was applied to 250 m MODIS NDVI time series (2000–2011) to assess modifications of natural vegetation cover. Finally, the Spearman's correlation was employed to determine the relationship of natural vegetation degradation with environmental factors. The study revealed a vast conversion of natural vegetation into agriculture (15.9%) and non-vegetated area (1.8%) between 1999 and 2011. Significant decreasing NDVI trends (p < .05) indicated negative modifications of natural vegetation (2000–2011 period) occurring along the protected areas borders and in fragmented landscapes characterized by disruption of continuity in natural vegetation. Spearman's correlation showed that accessibility, climatic and topographic conditions favored natural vegetation degradation. The results can enable the development of efficient land degradation policies. Graphical abstract: Highlights: The study area experienced vast conversion of natural vegetation into agriculture and non-vegetated area. In the period 2000-2011 significant negative modifications affected natural vegetation cover. Accessibility, climatic and topographic conditions favored natural vegetation degradation in the study area.